2019
DOI: 10.15283/ijsc19026
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Neural Networks in Immature Teeth with Non-Vital Pulp Following a Novel Regenerative Procedure

Abstract: Background and ObjectivesRecombinant amelogenin protein (RAP) was reported to induce soft-tissue regeneration in canine infected endodontically treated permanent teeth with open apices. To characterize identities of the cells found in the RAP regenerated tissues compared to authentic pulp by identifying: 1) stem cells by their expression of Sox2; 2) nerve fibers by distribution of the axonal marker peripherin; 3) axons by their expression of calcitonin gene–related peptide (CGRP); 4) the presence of astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The percentages of generated tissues were significantly different between the one and threemonth of evaluation periods (p<0.001). Our results support our previous studies where amelogenin showed enhanced regenerative ability compared to traditionally used CH treatment, with the advantage of regenerating pulp-like structure similar to the authentic pulp innervation, the expression of peripherin neuronal intermediate filaments (A-fibers) in the pulp periphery, CGRP-reactive central nerves (Cfibers) in the pulp core, the expression of Sox2 by pluripotent SCAP surrounding the growing roots, and regenerated stem cells inside the root canals [31][32][33] .…”
Section: Uppercase Super Script Letter Indicates Relation Between Categories Within the Variablessupporting
confidence: 90%
See 2 more Smart Citations
“…The percentages of generated tissues were significantly different between the one and threemonth of evaluation periods (p<0.001). Our results support our previous studies where amelogenin showed enhanced regenerative ability compared to traditionally used CH treatment, with the advantage of regenerating pulp-like structure similar to the authentic pulp innervation, the expression of peripherin neuronal intermediate filaments (A-fibers) in the pulp periphery, CGRP-reactive central nerves (Cfibers) in the pulp core, the expression of Sox2 by pluripotent SCAP surrounding the growing roots, and regenerated stem cells inside the root canals [31][32][33] .…”
Section: Uppercase Super Script Letter Indicates Relation Between Categories Within the Variablessupporting
confidence: 90%
“…RET in immature teeth with opened apexes and apical periodontitis is based on the potential to regenerate the dentin-pulp complex in the canal space, restoring the continuation of the tooth root development by both lengthening and thickening of the channel walls or apical closing, and resolving apical gingivitis, thus eliminating the patient's clinical signs and symptoms. In regenerative endodontics, cell homing appears to be the most promising strategy [32][33][34]. In the cell homing concept, endogenous cells of the organism are recruited to the empty canal via different biomaterials and biomolecules, which can achieve tissue repair/regeneration [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CBCT, it is worth mentioning the importance of the pulp vitality tests to identify REP success. Currently, most of the studies about regenerative endodontics evaluated repair issues, such as root development, rather than regenerative issues, such as the observed with pulp vitality (35). Some authors (36,37) reported the growth of a vital tissue inside of the root canal capable of responding to thermal (cold) and electric vitality tests in 50% of the cases (37).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (36,37) reported the growth of a vital tissue inside of the root canal capable of responding to thermal (cold) and electric vitality tests in 50% of the cases (37). However, histological information about the type of tissues formed in the root canal space and the vasculogenesis and neurogenesis process is still scarce (35).…”
Section: Discussionmentioning
confidence: 99%